(untitled) (LEGAL DIALOGICA, 2026)
Abstract : This study aims to determine and analyze the fulfillment of remission rights for inmates at Makassar Class IA Correctional Institution and identify factors that influence its implementation. This study uses an empirical research method. The results of the study The fulfillment of the right to reduce the sentence (remission) at Makassar Class IA Correctional Institution has basically been carried out in accordance with the provisions of Government Regulation Number 32 of 1999 and Minister of Law and Human Rights Regulation Number 3 of 2018. Remission is given to inmates who meet administrative and substantive requirements, and is proposed through the Correctional Database System (SDP) which makes the process more transparent and orderly. Factors that influence the implementation of the fulfillment of remission rights include internal and external factors. Internal factors include discipline, behavior,. External factors include limited officer resources, minimal development facilities, overcrowding conditions, and regulatory changes that have not been evenly understood. Research recommendations emphasize that remission is an important part of inmate development. It is necessary to increase institutional capacity, improve assessment standards and harmonize policies so that the implementation of remissions is more effective, fair and humane. Abstrak: Penelitian ini bertujuan untuk Mengetahui dan Menganalisis Pemenuhan Hak Remisi bagi Narapidana di Lembaga Pemasyarakatan Kelas I A Makassar serta mengidentifikasi faktor-faktor yang memengaruhi pelaksanaannya.Penelitian ini menggunakan Metode Penelitian Empiris.Hasil penelitian Pemenuhan hak pengurangan masa pidana (remisi) di Lembaga Pemasyarakatan Kelas I A Makassar pada dasarnya telah berjalan sesuai ketentuan PP Nomor 32 Tahun 1999 dan Permenkumham Nomor 3 Tahun 2018. Remisi diberikan kepada narapidana yang memenuhi syarat administratif dan substantif, serta diusulkan melalui Sistem Database Pemasyarakatan (SDP) yang membuat proses lebih transparan dan tertib.Faktor-faktor yang mempengaruhi terlaksananya pemenuhan hak remisi meliputi faktor internal dan eksternal. Faktor internal meliputi kedisiplinan, perilaku, dan partisipasi narapidana dalam program pembinaan. Faktor eksternal mencakup keterbatasan sumber daya petugas, minimnya sarana pembinaan, kondisi overcrowding, serta perubahan regulasi yang belum dipahami secara merata.Rekomendasi penelitian menegaskan bahwa remisi merupakan bagian penting dari pembinaan narapidana. Diperlukan peningkatan kapasitas lembaga, perbaikan standar penilaian dan harmonisasi kebijakan agar pelaksaan remisi lebih efektif, adil dan manusiawi